The Effectiveness of Propam’s Internal Oversight Mechanism in Ensuring Criminal Law Enforcement Accountability Among Members of the Indonesian National Police (A Study at the North Sumatra Regional Police) - Simbolon, Trilestaria; Rahman Maulana Siregar, Abdul; Rahmayanti (International Conference Epicentrum of Economic Global Framework, 2026)
Internal oversight of law enforcement institutions is a fundamental pillar of democratic governance. This study examines the effectiveness of the Professional and Security Division (Propam) as an internal oversight mechanism within the Indonesian National Police (Polri), with a particular focus on the North Sumatra Regional Police. The research employs a normative legal methodology, incorporating statute, conceptual, and case-based approaches, with primary legal materials drawn from legislation, police regulations, and court decisions relevant to police disciplinary enforcement. The findings reveal that while the normative framework governing Propam’s authority is relatively comprehensive anchored in Law No. 2 of 2002 on Polri and Government Regulation No. 2 of 2003 on Police Discipline its practical implementation faces significant constraints. These include a culture of institutional protectionism, limited independence of oversight panels, inadequate transparency in disciplinary proceedings, and an imbalance between internal and external accountability mechanisms. The study concludes that the current Propam oversight model requires structural reform, including stronger integration with external oversight institutions such as Komnas HAM and Ombudsman RI, as well as a paradigm shift toward human rights-based policing. Recommendations are directed at legislative reform and institutional restructuring to enhance both procedural and substantive accountability within Polri’s law enforcement conduct.